Model Matematika Kanker Paru-paru Akibat Pengaruh Sisa Asap Rokok dan Pencegahannya - Roni Al Maududi (Universitas Indraprasta PGRI Jakarta, 2017)
Lung cancer is one of the most common cancers that cause many death cases in the world. Cigarette smoke or secondhand smoke is one of the most important risk factors in the development of lung cancer. In this study, a Mathematical model for lung cancer represented by a non-linear system of differential equation is used to model the dynamics of a population which includes smokers. The basic reproduction number ( ) from the model will be determined and then by looking at this , we can analyze the sensitivity of the system by observing the parameters that can significantly change the value of . Numerical simulation using realistic data toward the model’s parameters will be provided to illustrate the dynamics of this population. The result of this study is a Mathematical model which can explain the dynamics of development of lung cancer in a population as a consequence of the existence of smokers and secondhand smoke in that population and the relevant efforts as prevention.